Primary cutaneous histoplasmosis difficult to treat in immunocompetent patient: case report and literature review - Batista,Jéssica Mauricio (2021)
ABSTRACT Histoplasmosis is an infection caused by the dimorphic fungus Histoplasma capsulatum. The disease is endemic in several regions of tropical and temperate climate. The fungus presents opportunistic behavior, causing widespread infection in immunocompromised patients, resulting from complication of primary pulmonary infection, due to exogenous reinfection or reactivation of a quiescent source. In immunocompetent individuals, approximately 95% of pulmonary infections are asymptomatic. However, prolonged exposure to high amount spores may lead to acute or chronic lung infection. Due to the low amount of inoculum, primary cutaneous histoplasmosis caused by traumatic implantation is extremely rare and effectively treated with triazoles. Thus, the present study aims to report a case of primary cutaneous histoplasmosis that is difficult to treat in an immunocompetent patient, and to review the literature on the incidence of drug-resistant Histoplasma capsulatum strains in clinical practice.